Boston Exchange Company Building at 49-57 State Street, ca. 1888 - Unknown (Tufts Archival Research Center, 2005)
Elevated view south-southeast of the Boston Exchange Company Building, located at 49-57 State Street. Signage adorns the facade of the building, which faces north-northwest. A street lamp is located on the sidewalk in front of the building. Demolition sites are located both to the east and west of the Boston Exchange Company Building. Copyprint 6 1/2 x 7 15/16, 8 x 10 overall Photographs